2016
DOI: 10.3892/ol.2016.4463
|View full text |Cite
|
Sign up to set email alerts
|

Choriocarcinoma of unknown origin with multiple organ metastasis and cerebral hemorrhage: A case report and literature review

Abstract: Abstract.A 26-year-old man was admitted to Beijing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In fact, syncytiotrophoblast in vitro are known to express Tissue Factor, the clotting initiator, and choriocarcinomas may be associated with thrombosis . It should be noted that both the absence of a tumor circulation on angiography and a lack of FDG‐glucose uptake on PET may argue against a diagnosis of cerebral metastasis. However, no tumor circulation is established in choriocarcinomas, and this might explain the negative imaging studies .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, syncytiotrophoblast in vitro are known to express Tissue Factor, the clotting initiator, and choriocarcinomas may be associated with thrombosis . It should be noted that both the absence of a tumor circulation on angiography and a lack of FDG‐glucose uptake on PET may argue against a diagnosis of cerebral metastasis. However, no tumor circulation is established in choriocarcinomas, and this might explain the negative imaging studies .…”
Section: Discussionmentioning
confidence: 99%
“…Cases of gestational, gonadal nongestational, or extragonadal primary choriocarcinomas in the liver, kidney, lung, or brain presenting with neurological impairment compatible with brain metastasis with intracranial hemorrhage have been reported . However, primary mediastinal choriocarcinoma is rare, and most often presents with symptoms such as coughing and chest pain .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the level of serumβ-HCG is elevated in different kinds of tumors, including renal cell carcinoma, [ 15 ] cervical squamous carcinoma, [ 16 ] ovarian cancer, [ 17 ] choriocarcinoma, [ 18 ] endometrial carcinoma, [ 19 ] sigmoid carcinoma, [ 20 ] lung cancer, [ 21 ] and so on.…”
Section: Discussionmentioning
confidence: 99%